2020
DOI: 10.1292/jvms.20-0043
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and physiological effects of alfaxalone intramuscular administration in cynomolgus monkeys (<i>Macaca fascicularis</i>)

Abstract: To evaluate the sedative and physiological effects of alfaxalone intramuscular (IM) administration, 12 healthy cynomolgus monkeys were administered single IM doses of alfaxalone at 0.625 mg/kg (ALFX0.625), 1.25 mg/kg (ALFX1.25), 2.5 mg/kg (ALFX2.5), 5 mg/kg (ALFX5), 7.5 mg/kg (ALFX7.5), or 10 mg/kg (ALFX10); saline was used as the control (CONT). The sedative effects were subjectively evaluated using a composite measure scoring system in six animals. Changes in respiratory rate, pulse rate, non-invasive blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Our group switched to this combination for the final two NHPs. Short-term NHP studies have shown that at low to moderate doses, alfaxalone preserves heart rate and mean arterial pressure, while producing effective sedation and analgesia [30][31][32]. Alfaxalone does appear to reduce cerebral blood flow and contribute to hypothermia, with higher doses also exerting suppressive cardiovascular effects [30][31][32].…”
Section: Plos Onementioning
confidence: 99%
“…Our group switched to this combination for the final two NHPs. Short-term NHP studies have shown that at low to moderate doses, alfaxalone preserves heart rate and mean arterial pressure, while producing effective sedation and analgesia [30][31][32]. Alfaxalone does appear to reduce cerebral blood flow and contribute to hypothermia, with higher doses also exerting suppressive cardiovascular effects [30][31][32].…”
Section: Plos Onementioning
confidence: 99%
“…It shows certain benefits compared to other anesthetic agents due to a broad margin of safety and a low cumulative effect after repeated doses, which enables a rapid recovery (Lau et al, 2013;Ferre et al, 2006;Rezende, 2015). Alfaxalone is used for both induction and maintenance of anesthesia in many species including companion and experimental animal species such as dog (White and Yates, 2017), cat (Khenissi et al, 2017), goat (Abouelfetouh et al, 2021), sheep (Andaluz et al, 2012), pig (Bigby et al, 2017), horse (Goodwin et al, 2011), rhesus macaque (Bertrand et al, 2017), cynomolgus monkey (Casoni et al, 2015), and common marmoset (Bakker et al, 2013). Alfaxalone anesthesia has minimal negative impact on the cardiorespiratory system though it can cause hypoxemia if administrated in high doses (Wada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alfaxalone is used for both induction and maintenance of anesthesia in many species including companion and experimental animal species such as dog (White and Yates, 2017), cat (Khenissi et al, 2017), goat (Abouelfetouh et al, 2021), sheep (Andaluz et al, 2012), pig (Bigby et al, 2017), horse (Goodwin et al, 2011), rhesus macaque (Bertrand et al, 2017), cynomolgus monkey (Casoni et al, 2015), and common marmoset (Bakker et al, 2013). Alfaxalone anesthesia has minimal negative impact on the cardiorespiratory system though it can cause hypoxemia if administrated in high doses (Wada et al, 2020). It is also commonly used without side effects in pregnant dogs showing no negative effects on the stability of maternal and fetal hemodynamics (Andaluz et al, 2013;Metcalfe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%